Effect of Biopesticides Against Sucking Insect Pests of Brinjal Crop Under Field Conditions - S. Shahzad Ali; Sher Ahmad; S. Sohail Ahmed; Huma Rizwana; Saima Siddiqui; S. Shahbaz Ali; Irshad Ali Rattar; Munawer Ali Shah (Journal of Basic & Applied Sciences, 2016)
A field study was carried out during 2013 at the experimental area of Entomology Section, Agriculture Research Institute, (ARI) Tando Jam to examine the effect of bio-pesticides against sucking insect pests of brinjal crop under field conditions. Five treatments with three replications were applied. The treatments were: T1=chemical control (confidor/Diamond), T2=Neem (Azadirachta indica), T3= Tobacco (Nicotiana tabacum), T4= Eucalyptus (Eucalyptus globus), T5= Untreated (Control). Three insect pests were found infesting brinjal including white flies, jassid and mites. Pre treatment- and post-treatment observations were recorded. The results revealed that against white fly, the first spray of chemical control(confidor) showed highest reduction percent (96.62%) followed by Neem extract (82.60%), Tobacco extract (75.95%), Eucalyptus extract (73.93%) and lowest for untreated control (11.07%); while in the second spray also, chemical control(Diamond) showed highest effect against white fly (78.32%); followed by Neem extract (67.53%), Tobacco extract (56.43%), Eucalyptus extract (42.25%) and least by untreated plot (5.49%). Against jassid, chemical control (confidor) showed highest effect (77.90%) as observed during 1st spray, followed by Neem extract (55.95%), Tobacco extract (53.38%), Eucalyptus extract (53.99%) and untreated control (8.00%), while after second spray also chemical control (Diamond) showed highest reduction percent (81.70%) followed by Neem extract (68.73%), Tobacco extract (55.72%), Eucalyptus extract (50.66%) and the lowest was resulted by untreated control (13.91%). Against mites population on brinjal the first spray results showed that chemical control (confidor) showed highest effect (98.19%) followed by Neem extract (96.19%), Tobacco extract (95.75%), Eucalyptus extract (86.86%) and least population was recorded in untreated control (9.96%). After second spray, chemical control (Diamond) showed highest reduction percent (99.65%), followed by Neem extract (98.33%), Tobacco extract (92.85%), Eucalyptus extract (88.93%) and the lowest reduction percent was resulted by untreated control (9.14%) respectively. Chemical control (confidor/Diamond) showed its superiority in effect to combat sucking insect pests studied in brinjal, followed by Neem extract, Tobacco extract, Eucalyptus extract and untreated control remained the least.